(untitled) (Baghdad Science Journal, 2025)
This study was carried out to evaluate the antioxidant activity of Iraqi sumac seeds (Rhus coriaria. L) (Anacardiaceae). Total phenolic compounds and flavoniods were determined in three different sumac seed extracts (SSE) (aqueous,ethanolic and methanolic extract). For extraction Antioxidant activity of SSE were evaluated by various antioxidant assays, including total antioxidant capacity, reducing power,by using 1,1-diphenyl-2-picryl hydrazyl (DPPH) radical scavenging, nitric oxide scavenging, Hydroxyl radical scavenging, and metal ion chelating activities. These various antioxidant activities were compared with ascorbic acid as a standard antioxidant.The results showed that the three(SSE), contained large amounts of phenolic and flavoniods compounds. The results also showed that the three( SSEs ) have antioxidant activities , the methanolic (SSEs) contain larger amounts of phenolic and flavoniod compounds and have a higher antioxidant activities than that of aqueous or ethanolic (SSE).These results indicated that Iraqi aqueous and alcoholic extracts of Iraqi sumac in especial methanolic) SSE( are good scavengers for reactive oxygen species(ROS) and are a potential source of natural antioxidant, that may be used in pharmaceutical or food industry .